Communication Industry in Exploring Brilliant Ideas in an Organized Room - Sri Prasetyo Widodo; Edison Hatogaon Manurung; Reinhard Manurung; Muchamad Mukhlis; Noval Apriansa; Stephanie Putri Deasy Chandrayani Jachnis; Khairani Aisyah Rasyad; Muhamad Wahyudi; Aldinda Firda Nisa Sena Putri (Indonesian Journal of Advanced Social Works, 2023)
Real Work Lecture (KKN) is an intra-curricular form which is an implementation of the Tridharma of Higher Education to provide students with work and learning experiences in community empowerment. The KKN activities carried out in the workspaces of the Faculty of Engineering Lecturers and the Laboratory of the Faculty of Communication are dedicated to the development of the communications industry, is expected to create brilliant ideas at work and facilitate the practice of communication science in a room that has been arranged and tidied up during the KKN activities which lasted for approximately three weeks. This activity was a challenge in itself for the KKN group by renovating the Engineering Faculty office space and Fikom Laboratory in order to create a space that can inspire its users and can work or be a creatif in a more inspiring, innovative and educative in a well-organized room.